Why is the histomorphological diagnosis of small salivary gland tumours so much more difficult? Warum ist die histomorphologische Diagnostik von Tumoren kleiner Speicheldrüsen so viel schwieriger? - Ihrler, Stephan; Agaimy, Abbas; Guntinas-Lichius, Orlando; Haas, Christian; Greber, Lukas (Die Pathologie, 2023)
There is a widespread impression among clinicians and pathologists that the histomorphological diagnosis of minor salivary gland tumours is more difficult and more frequently misdiagnosed than that of major glands. This is based on subjective clinical impression; scientific proof of and potential reasons for this difference are lacking. We identified 14 putative clinical, histopathological and combined clinical–histological reasons and four consequences, which together could explain the perceived greater difficulty of diagnosing minor gland tumours. We performed a thorough literature search and a statistical comparison of data from a personal large consultation series (biased for “difficult” cases) with cumulated data from a routine, unselected (non-consultation) series from the literature. Through this comparison, we could prove with statistical significance a series of reasons and consequences for this greater diagnostic difficulty in minor glands. Frequent incisional biopsies, almost obligatory low-grade bland cytology in malignant tumours and insufficient clinical–pathological communication emerged as the most important reasons. The special anatomic location of the hard palate contributes to further diagnostic difficulties, such as tumour necrosis, mucosal ulceration, pseudoinvasion and the “tumoural-mucosal fusion” phenomenon. Knowledge of these pitfalls in clinic and pathology can help overcome these difficulties and reduce the misdiagnosis rate in minor gland tumours. Our findings result in a series of recommendations both for the clinic and pathology.
CRIS-Team Scopus Importer:2023-07-28
Keywords: Biopsy; Diagnostic errors; Molecular pathology; Palate; Salivary gland neoplasms